Natura współczesnych zmian jako źródło wyzwań w zarządzaniu przedsiębiorstwem - Suszyński, Cezary (Nature of present changes as a source of challenges in management, 2006)
The paper underlines stochastic and lateral nature of present changes, as well as discontinuity as key features influencing activities and management of companies operating within the developed market economy. Following this observations the four aspects of changes are discussed: the pressure for change, difficulties to manage change, the risk of change and the future of change. As far as the last aspect (the future of change) is considered a model of open, flexible organization, developing its human resources and implementing modern communication teclmologies seems to be highly recommended.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 487-495